Da mente dos historiadores às mãos dos autores: livros didáticos de história e suas apropriações historiográficas sobre os africanos escravizados no Brasil (1890-2010) - Schmitz, Zenaide Inês (2021)
This thesis focuses on the context of the relationships established between historiography and History textbooks in Brazil. The main objective is to analyze how History textbooks appropriated the production forms and circulation of the different approaches proposed by historiography on enslaved Africans in the country in the period between 1890 and 2010. The documentary corpus consists of 24 books, two of each decade of the defined period. The theoretical-methodological support adopted Cultural History approaches, mainly the contribution of Roger Chartier (1990; 1991; 2010), who, when looking at this field, operates with the concepts of representations, practices, and appropriations. History textbooks, taken here as an object and source, were analyzed according to five categories: African Diaspora, Resistance, Daily Life of the Slaves, Abolitionism, and Post-abolition Context. It was possible to verify that the theme of enslaved Africans has repercussions on the works taken here as a source of research and that these maintain a dialogue with the theoretical and historiographic debate that occurs in different spheres. History textbooks from the period 1890 to 2010 assimilated their way, to a larger or smaller extent, in different rhythms and formats, the changes that occurred in historiography. The research demonstrated that from classical and revisionist historiography came the appropriation of African representations only in the slavery context. If it was not enough, in most cases, it is characterized as an object or merchandise, based on the thesis of captive's reification. With the renovation of Brazilian historiography from the 1980s, the History textbook began to gain new characteristics. This is presented in a perspective of seeing the enslaved as historical subjects insofar. It portrays their cultural and ethnic contributions in the constitution of the Brazilian people and recognizes it as positive the cultural diversity and plurality that characterize them. However, besides historiography, other forms of intelligibility present in each era's historical culture and current social practices also affect this cultural object. In this direction, History textbooks present themselves in disharmony with the knowledge constructed by social movements and by other knowledge communities. Keywords: Representations; Practices; Appropriations; Enslaved Africans; Historiograph